Legal Analysis Of Copyright Of Artificial Intelligence (Ai) Digital Works As An Object Of Fiduciary Guarantee - Pratama, Anugerah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The development of digital technology and the creative economy has made copyright, including Artificial Intelligence (AI)-based works, an economically valuable asset with the potential to be utilized in financing activities. Normatively, based on Law Number 28 of 2014, copyright is an intangible movable object that contains economic rights and can be transferred. Furthermore, Law Number 42 of 1999 provides space for intangible movable objects to be used as fiduciary collateral. Thus, legally, digital copyright meets the qualifications as an object of fiduciary collateral. This research uses a normative juridical method with a statutory and conceptual approach. The research data is sourced from primary, secondary, and tertiary legal materials, which are analyzed descriptively and analytically to examine the regulation of copyright on AI works and their relationship to fiduciary guarantee law in Indonesia. The research results show that copyright on digital works based on Artificial Intelligence normatively meets the qualifications as an object of fiduciary guarantee because it is an intangible movable object containing economic rights and can be transferred. However, its implementation in practice still faces obstacles in the form of the absence of technical regulations regarding the burden mechanism, intangible asset valuation standards, and certainty of execution in the event of default. Thus, strengthening regulations and technical guidelines is needed to ensure legal certainty in the use of digital copyright as an object of fiduciary guarantee.